THE PURSE-SEINE FISHERY FOR OIL SARDINE IN THE SOUTH KARNATAKA COAST AND ITS EFFECTS ON THE INDIGENOUS FISHERY - Dhulkhed, M H; Bhat, K Uma (Indian Journal of Fisheries, 2011)
With the introduction of purse seines in the midseventies the catches of oil sardine steeply rose from 6,129 t in 1976-77 to 32,629 t in 1979-80. However, in the subsequent year the landings declined by 6,800 t and with increase in effort the catch rate only showed a downward trend, obviously because of the large-scale removal of gravid fish during 1978-79 and 1979-80. The total instantaneous rate of mortality was found to be high indicating the high rate of mortality caused by the gear. The adverse effect of purse seiners on traditional fishery, with special reference to the shore-seine Rampart, is discussed